Terrestrial mammals’ species richness, diversity, and activity patterns in the Darién National Park, Panamá - Moreno, Ricardo; Young, Natalia; Puertes, Arturo; de la Torre, J. Antonio (Therya Notes, 2023)
Darién National Park is one of the largest forest blocks of Mesoamerica. Monitoring terrestrial mammal species in this region is essential to define adequate conservation actions to ensure their long-term persistence. We deployed 33 camera trap stations at the Darién National Park and evaluated the relative abundance of terrestrial mammal species, the sampling effort needed to estimate reliable richness estimates, and the activity patterns of the most recorded species. We identified with certainty 24 species of terrestrial mammals. Our survey was quite representative since we detected 85 % of the species that had previously been recorded for this area. Jaguars (Panthera onca), ocelots (Leopardus pardalis), and margays (L. wiedii) showed crepuscular behavior, and pumas (Puma concolor) and jaguarundis (P. yagouaroundi) showed diurnal behavior. Species that showed more activity during periods of more light were the ñeque (Dasyprocta puntancta), coati (Nasua narica), temazate (Mazama temama), and both species peccaries (Tayassu pecari and Pecari tajacu). Species with more nocturnal activity were the paca (Cuniculus paca), nine-banded armadillo (Dasypus novemcinctus), and Baird’s tapir (Tapirus bairdii). This one of the first studies that evaluates the activity patterns of terrestrial mammals in the Darién and Panamá. We recorded some species that have not been documented in previous camera trapping studies for the region. However, the richness estimators indicated that there are still species that could be detected. Implementation of long-term monitoring programs is a crucial step to better understanding the dynamics of wildlife populations in the region.